Caracterização socioeconômica da produção primária da cadeia produtiva da soja no Município de Uruçui-PI - Rodrigues, Miguel Antônio (2015)
The search for the exacerbated economic growth generates consequences that compromise the quality of life on the planet. In recent decades, agribusiness has emerged as one more element which accentuated the imbalances in the environmental and social spheres. In this scenario, traditional landowners expanded their agricultural frontiers to areas not previously explored in this dimension: Piauiense Cerrado, which had the flagship exploration soy cultivation on a large scale. Thus, the research aimed to study certain social and economic impacts of the primary chain of soybean production in a representative sample service units in New District of the city of Santa Rosa Uruçuí-IP. The study methodology was given through specialized bibliographic research on the issue, associated with data collection and primary nature of information obtained from 55 Units District Soybean Producers New Santa Rosa, in Uruçuí-IP. The study methodology was given through specialized bibliographic research on the issue, associated with data collection and primary nature of information obtained from representative 55 Units District Soybean Producers New Santa Rosa, in Uruçuí-PI. These dimensions were divided into two strata. The data collected were subjected to descriptive statistics, through the central measures of value calculation and dispersion for quantitative variables was identified and the dominant spectrum of qualitative variables separately for each dimension of the substrate. Then took place the Principal Component Analysis to know the importance of each variable studied on the total variance available by defining factors. It was found that there is great heterogeneity among the service units, which concentrated 78,71% of the total variation, especially for Land Surface Net, and the proportion of cultivated cereals, resulting in a variation of the variable expenses. Generally, it can be seen that there are a variety of differentiation between Lend Lords and Meium owners, focusing mainly on the advantages with which those operating in respect of these. The research was characterized by indicative of exogenous economic growth. Identified the role of a multinational company that monopolizes the marketing of grain in the District.